When Positive Thinking Changes Perspective: Parental Acceptance of Children with Special Needs - Bunari, Elsha Sandra; Widyana, Rahma; Purnamasari, Santi Esterlita (Universitas Islam Negeri Raden Intan Lampung, 2024)
There is a gap between parents' expectations of having a healthy and normal child and the reality of having a child born with an intellectual disability. This condition often triggers negative emotional responses such as denial, guilt, and frustration among parents. The inability to accept the child's condition frequently leads to suboptimal parenting, which negatively affects the child's development. Therefore, an effective psychological intervention, such as positive thinking training, is needed to help parents improve their acceptance of children with intellectual disabilities. This study aims to examine the differences in the level of parental acceptance before and after participating in positive thinking training. The research design used was a one-group pretest-posttest design. The subjects consisted of eight parents of children with intellectual disabilities who initially had low scores in parental acceptance. The measurement tool used was the Parental Acceptance Scale, which consists of 48 items with a reliability of 0.957. Data were analyzed using the Wilcoxon T-Test. The results showed a significant difference in parental acceptance scores before and after the training, with a z-value of 2.525 (p < 0.005). Keywords: Parental Acceptance, Positive Thinking Training, Children with Intellectual Disabilities